2007
DOI: 10.1007/s10802-007-9146-z
|View full text |Cite
|
Sign up to set email alerts
|

Are Motor Inhibition and Cognitive Flexibility Dead Ends in ADHD?

Abstract: Executive dysfunction has been postulated as the core deficit in ADHD, although many deficits in lower order cognitive processes have also been identified. By obtaining an appropriate baseline of lower order cognitive functioning light may be shed on as to whether executive deficits result from problems in lower order and/or higher order cognitive processes. We examined motor inhibition and cognitive flexibility in relation to a baseline measure in 816 children from ADHD and control families. Multiple children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
100
4
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 83 publications
16
100
4
3
Order By: Relevance
“…In contrast, we found that children with ADHD made significantly more errors and were more variable in their response speed than children without ADHD. This is a finding that has frequently been reported by others in a diversity of neuropsychological tasks (Rommelse et al, 2007;Sergeant et al, 2003;van der Meere, 2005). The absence of significant group differences in correct versus error RT suggests that the higher error rate in children with ADHD was not due to more impulsive behaviour.…”
Section: Behavioural Datasupporting
confidence: 83%
See 2 more Smart Citations
“…In contrast, we found that children with ADHD made significantly more errors and were more variable in their response speed than children without ADHD. This is a finding that has frequently been reported by others in a diversity of neuropsychological tasks (Rommelse et al, 2007;Sergeant et al, 2003;van der Meere, 2005). The absence of significant group differences in correct versus error RT suggests that the higher error rate in children with ADHD was not due to more impulsive behaviour.…”
Section: Behavioural Datasupporting
confidence: 83%
“…In addition, it has been claimed that no evidence of a response inhibition deficit can be found when tasks with an experimental manipulation of inhibition load are used and performance is compared to a control condition (Rommelse et al; Van De Voorde, Roeyers, Verté, & Wiersema, in press). The latter has also been found for other executive function (EF) deficits that are frequently attributed to ADHD, such as deficits in working memory (Karatekin, Bingham, & White, 2009;Klein, Wendling, Huettner, Ruder, 4 & Peper, 2006;Shallice et al, 2002;Van De Voorde et al, in press) and cognitive flexibility (Rommelse et al, 2007). With respect to RD, there have been reports of additional deficits that cannot easily be explained by a pure phonological deficit.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Three computerized tasks of the Amsterdam Neuropsychological Tasks (ANT) system were used to quantify attention/alertness, motor coordination, and executive functions [2,3]. Alertness was evaluated by the mean of the reaction time (msec) to 32 visual stimuli and the inconsistency of alertness by the standard deviation of the 32 reaction times.…”
Section: Emethods 3 Tests and Questionnaires To Assess Neurocognitivmentioning
confidence: 99%
“…Children who have been critically ill at young age suffer from a substantial neurocognitive deficit when assessed years after admission to the pediatric intensive care unit (PICU) [1][2][3][4][5]. This neurocognitive legacy comprises, besides lower scores for intelligence, visual-motor integration, memory and behavior, also an important deficit in executive functions, motor coordination and attention [1].…”
Section: Introductionmentioning
confidence: 99%